Point‐of‐care lung ultrasound in the assessment of patients with COVID‐19: A tutorial. Issue 4 (27th October 2020) - Cid, Ximena; Wang, Andrew; Heiberg, Johan; Canty, David; Royse, Colin; Li, Xiaoqiang; El‐Ansary, Doa; Yang, Yang; Haji, Kavi; Haji, Darsim; Denault, Andre; Tivendale, Lynda; et al.
Abstract: The adoption of point‐of‐care lung ultrasound for both suspected and confirmed COVID‐19 patients highlights the issues of accessibility to ultrasound training and equipment. Lung ultrasound is more sensitive than chest radiography in detecting viral pneumonitis and preferred over computed tomography for reasons including its portability, reduced healthcare worker exposure and repeatability. The main lung ultrasound findings in COVID‐19 patients are interstitial syndrome, irregular pleural line and subpleural consolidations. Consolidations are most likely found in critical patients in need of ventilatory support. Hence, lung ultrasound may be used to timely triage patients who may have evolving pneumonitis. Other respiratory pathology that may be detected by lung ultrasound includes pulmonary oedema, pneumothorax, consolidation and large effusion. A key barrier to incorporate lung ultrasound in the assessment of COVID‐19 patients is adequate decontamination of ultrasound equipment to avoid viral spread. This tutorial provides a practical method to learn lung ultrasound and a cost‐effective method of preventing contamination of ultrasound equipment and a practical method for performing and interpreting lung ultrasound.